2016
DOI: 10.18632/oncotarget.12409
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia-induced CCL28 promotes recruitment of regulatory T cells and tumor growth in liver cancer

Abstract: Tumor cells craft microenvironment to overcome growth disadvantages and adjust to escape the immunosurveillance during tumorigenesis and metastasis. The evolving adaption to the changing microenvironment is exemplified by the development of strategies to deal with hypoxia resulted from fast proliferation of the tumor cells. In this study, we found that hypoxia hepatocellular carcinoma (HCC) cells recruited Regulatory T cells (Tregs) and expressed more Chemokine (C-C motif) ligand 28 (CCL28). Deletion of CCL28 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
87
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(99 citation statements)
references
References 32 publications
4
87
0
Order By: Relevance
“…In addition, immunosuppression and increased number of Tregs were found in glioblastoma multiforme under hypoxic conditions . Hypoxia has been reported to be required for Treg cells to induce tumor and Treg‐induced angiogenesis via stimulation of chemokine (C‐C motif) ligand 28 expression . In Treg cells of nasal polyps, the expression of RORγ and HIF‐1α is increased and their levels show positive correlation to each other .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, immunosuppression and increased number of Tregs were found in glioblastoma multiforme under hypoxic conditions . Hypoxia has been reported to be required for Treg cells to induce tumor and Treg‐induced angiogenesis via stimulation of chemokine (C‐C motif) ligand 28 expression . In Treg cells of nasal polyps, the expression of RORγ and HIF‐1α is increased and their levels show positive correlation to each other .…”
Section: Discussionmentioning
confidence: 99%
“…Human studies have shown that a variety of chemokines derived from tumour cells and/or tumour microenvironments were involved in specific recruitment of Tregs . The CC chemokines CCL5, CCL20, CCL22 and CCL28 promote Treg infiltration into human tumour tissues through their receptors on Tregs, CCR5, CCR6, CCR4 and CCR10, respectively . In addition, CXC chemokines CXCL9, CXCL10 and CXCL11 induce Treg infiltration through CXCR3 …”
Section: Discussionmentioning
confidence: 99%
“…Regulatory T-cells (T-reg) are CD4+/CD25+/FOXP3 +immune-suppressive T-cells whose accumulation in HCC is associated with disease progression [56] and reduced survival [31,57]. They are recruited intratumorally via CCL17/CCL22 secretion by tumour associated macrophages (TAMs) [58,59]. In addition, T-reg differentiation is promoted by the production of TGF-β, IL-10 and other mediators including COX-2 and indoleamine 2,3-dioxygenase by stromal and tumour cells [60].…”
Section: Regulatory T-lymphocytesmentioning
confidence: 99%